Developing an integrated phage-PCR assay for rapid detection of Listeria monocytogenes in foods - El Emam, Mohamed M. (2013)
Listeria monocytogenes is a common food borne pathogen which is an important contaminant found in various food factory environments, because of its ability to survive in a wide range of environmental conditions, and to grow at refrigeration temperatures. L. monocytogenes has caused both occasional outbreaks and sporadic cases of food-borne illness characterised by high mortality rates. In the UK and other European countries, there has been a conspicuous rise in the number of reported cases of “Listeriosis” recently. Hence, development of efficient and rapid methods for detection of this microorganism in various foods is of great significance for the food industry; and is needed to ensure the safety of foods that are considered at high risk of contamination. Conventional bacteriological methods (e.g. ISO 11290-1/A1) for the detection and quantification of L. monocytogenes are laborious and time consuming. Therefore, development of a rapid and reliable test capable of detecting very low numbers of the organism in ready-to-eat products is required. To address this, a phage amplification assay has been developed as a rapid method for the detection of L. monocytogenes using the broad host range phage A511. Successful development of the assay required identification of a virucide that could achieve inactivation of the phage without affecting the viability of the target cell to be detected. Several different substances were evaluated as potential virucides, and among the tested materials, tea infusions were found to be the most effective virucidal agent for this experiment. The efficacy of the new assay was tested using Stilton cheese, as a representative high risk dairy product, and a method was developed to use centrifugation to concentrate bacterial cells present in samples of half-Fraser broth enrichments. The cells were detected by using the new phage amplification assay and this combination of techniques was shown to be able to detect low numbers of cells in shorter times than can be achieved using conventional culture methods. An additional molecular identification step was also developed so that the identity of the cells detected could be confirmed using a multiplex PCR which targeted conserved regions of the Listeria 16S rDNA genes. In this assay, two amplified DNA fragments were generated confirming the presence of Listeria genus (400 bp band) and also L. monocytogenes species (287 bp band). An advantage of this combined phage-PCR method its ability to detect only viable cells in food samples. The combined assay was then tested on a wide range of spiked food samples, including Camembert cheese, pasteurised milk, minced meat, turkey meat and smoked salmon. The obtained results showed that the limit of detection was as low as 20 (± 5) cfu per 25 g, and duration needed for the detection and molecular conformation of speciation was 2 days (44 h), compared to 5 days using conventional culture methods. The combined phage-PCR assay was able to achieve a sensitive and specific identification of viable L. monocytogenes present in foods within 48 h, and therefore would allow for rapid screening of food products prior to release from the factory.